(3EOGQI GdeNGWQ (B:s (3YbhO GdNjGQGJ (B/s - (3gfOj, efjQ GHQGgjes ((3GdGScfOQjI(B: s (3ecJHI GdeYGQa(B, s, 2007)
(3jVe YbhO GdNjGQ Ydi GdCSge, GSJQGJjLjGJ NjGQGJ eJbOeI, YbhO GdNjGQGJ Ydi CSYGQ GdUQa, YbhO GdNjGQGJ Ydi GdYedGJ, JSYjQ YbhO GdNjGQ Ydi CSYGQ GdUQa, YbhO GdNjGQ Ydi CSYGQ GdaGFOI hGdCUhd PGJ SYQ GdaGFOI, YbhO GdNjGQ Ydi eDTQGJ GdCSge, YbhO GdNjGQ Ydi eDTQGJ GdCSge, JCejf GdeMaXI, GdYbhO GdeJOGhdI aj GdGShGb ZjQ GdefXeI, bQGQGJ GdESJKeGQ hGdJehjd aj eaghe YbhO GdNjGQGJs
(3cTGa eUWdMGJ U(B.691s
Keywords: (3GdCSges; (3GdYbhOs; (3GdeNGWQ GdeGdjIs